Ranking of Tariffs Under Monopoly Power in Trade: An Extension - Riley, John G. (Quarterly Journal of Economics, 1970)
Journal Article Ranking of Tariffs Under Monopoly Power in Trade: An Extension Get access John G. Riley John G. Riley Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 84, Issue 4, November 1970, Pages 710–712, https://doi.org/10.2307/1880855 Published: 01 November 1970